2021
DOI: 10.1177/20451253211035269
|View full text |Cite
|
Sign up to set email alerts
|

Asenapine: an atypical antipsychotic with atypical formulations

Abstract: Asenapine is a second-generation (atypical) antipsychotic medication not available in a pill that can be swallowed; rather, it is commercialized in sublingual and transdermal formulations. This is a consequence of extensive first-pass metabolism if ingested. The sublingual formulation is approved in many jurisdictions for the treatment of schizophrenia and manic or mixed episodes associated with bipolar I disorder and is available generically. The efficacy profile is well characterized in a number of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 72 publications
(160 reference statements)
1
9
0
Order By: Relevance
“…Transdermal antipsychotics have the potential to enhance treatment adherence, so the US Food and Drug Administration approved transdermal asenapine in 2019 for the treatment of schizophrenia in adults ( Musselman et al , 2021 ). Its possible place in real-world practice has been sought.…”
Section: Discussionmentioning
confidence: 99%
“…Transdermal antipsychotics have the potential to enhance treatment adherence, so the US Food and Drug Administration approved transdermal asenapine in 2019 for the treatment of schizophrenia in adults ( Musselman et al , 2021 ). Its possible place in real-world practice has been sought.…”
Section: Discussionmentioning
confidence: 99%
“…Data from this phase III DBRCT using sublingual asenapine showed akathisia and overall DIMD rates as high as 7.7% and 10%, respectively, during a 12–16-week open label period (n = 549) and 1.6% and 2.4%, respectively, during the 26-week double-blind phase (n = 253) relative to 0.8% in the placebo group [ 139 ]. Other studies (n = 80–532) in both schizophrenia and bipolar mania or mixed episodes showed similar rates of these AEs and minimal changes in motor rating scales [ 138 ]. No reports were found of tardive syndromes are associated with transdermal asenapine.…”
Section: Incidence Of Dimd With Alternative Formulations Of Antipsych...mentioning
confidence: 93%
“…Patches are applied daily with equal hepatic and renal metabolism [ 137 ]. It antagonizes multiple receptors including 5-HT 2A/2B/2C/6/7 , D1/D2/D3Rs, and α 1 /α 2a/b/c adrenergic receptors with dose-dependent D2R occupancy [ 138 ].…”
Section: Incidence Of Dimd With Alternative Formulations Of Antipsych...mentioning
confidence: 99%
“…Although generally similar, the side effect profiles of these SGAs do vary. For example, compared with other SGAs, asenapine poses relatively less risk of parkinsonism, dystonia and anticholinergic effects but relatively more weight gain and glucose abnormalities 39. Risperidone poses a higher risk of hyperprolactinaemia but relatively fewer anticholinergic side effects 40.…”
Section: Other Common Treatments For Bd-dmentioning
confidence: 99%
“…For example, compared with other SGAs, asenapine poses relatively less risk of parkinsonism, dystonia and anticholinergic effects but relatively more weight gain and glucose abnormalities. 39 Risperidone poses a higher risk of hyperprolactinaemia but relatively fewer anticholinergic side effects. 40 Clozapine carries a higher risk of weight gain, glucose abnormalities, hyperlipidaemia, anticholinergic side effects, sedation, agranulocytosis and electrocardiographic abnormalities, including QT interval prolongation.…”
Section: Classic Mood Stabilisersmentioning
confidence: 99%